The CD45 77C/G allele is not associated with myasthenia gravis - a reassessment of the potential role of CD45 in autoimmunity - Hammarström Lennart; Pirskanen Ritva; Ramanujam Ryan (BMC Research Notes, 2010)
Abstract Background The G allele of the CD45 77C/G SNP (rs17612648), which has previously been suggested to be associated with autoimmune disorders, was genotyped in 446 Swedish myasthenia gravis (MG) patients and 2303 matched controls. Results There was no association between the polymorphism and patient group as a whole (p = 0.199), nor with clinical subgroups. Our results add to a growing number of studies unable to find association between the 77C/G polymorphism and autoimmune disorders. One control sample, from an adult blood donor, was homozygous for the G allele, yet negative for a panel of auto-antibodies, representing the first homozygous individual studied in this respect. Conclusions The 77C/G mutation does not predispose to MG, and its role in autoimmunity may have to be re-evaluated.